P021 COMPLEMENTARY AND ALTERNATIVE MEDICINE IN INFLAMMATORY BOWEL DISEASE: WHERE'S THE DISCUSSION?. (18th January 2018) - Al-Abbas, Bedoor; Dave, Jenny; Alsulaimi, Najwan; Almedimigh, Abdulaziz; Myint, Aung; Borum, Marie L
Abstract: Background: The role of complementary and alternative medicine (CAM) have been used as adjunctive treatment in inflammatory bowel disease (IBD). It is estimated that 30–50% of IBD patients have used CAMs at some point in their disease course. However, it has been estimated that <50% of CAM users discuss this therapeutic strategy with their gastroenterologists. This study evaluated the frequency at which physicians discuss CAM with their IBD patients. Methods: A medical record review of consecutive IBD patients seen at a university gastroenterology practice during a 6 month period was performed. Patient age, gender, ethnicity and disease type (Crohn's disease, ulcerative colitis, indeterminate colitis) were obtained. Records were reviewed for use of or discussion about CAM. A database was created maintaining patient confidentiality. The study was approved by the university IRB. Results: Medical records of 268 patients (118 men, 150 women) with a mean age of 43 were reviewed. There were 158 Crohn's, 109 ulcerative colitis (UC), 1 indeterminate colitis. There were 143 white, 80 African-Americans, 6 Hispanic, 10 Asian and 29 with unspecified ethnicity. Five patients (1.87%) had documentation of CAM use (3 with probiotics, 2 with herbal supplements). All patients with documentation of CAM use were white. There was no difference in the frequency of CAM use based upon gender (p=0.6577; 3 males, 2 females) or disease type (p=0.4012; 3 UC, 2 Crohn's disease). Conclusion: CAM use in IBD is frequently used, but infrequently discussed with patients. This study suggests that IBD patients rarely used CAM. However, it is possible that there is patient reluctance to disclose CAM use due to perceived lack of physician awareness or acceptance. Additionally, physicians may infrequently discuss or document CAM treatments. It is important that there are efforts to increase CAM discussion among IBD patients to fully appreciate therapeutic strategies used by patients.